An epidemiological analysis of the injury pattern in indoor and in beach volleyball - Aagaard, H.; Scavenius, M.; Jorgensen, U. (International Journal of Sports Medicine, 1997)
This study was designed to evaluate the injuries in indoor and in beach volleyball, and to compare the injury pattern in the two different types of volleyball. Injuries in 295 volleyball players were recorded during the beach volleyball season 1993 and during the following indoor volleyball season 1993 to 1994. The method of enquiry was two identical questionnaires. Equal numbers of men and women, elite and recreational players were represented. In beach volleyball 24 injuries were reported and 286 in indoor volleyball, representing an incidence of 4.9 injuries per 1000 volleyball hours in beach volleyball and 4.2 in indoor volleyball. The most frequent injuries were acute injuries located in the ankle and finger and overuse injuries in the knee and shoulder. The injury pattern was different in indoor and in beach volleyball. In beach volleyball most injuries occurred in field defence and in spiking, with overuse injuries in the shoulder as the major site. In indoor volleyball most injuries occurred during blocking and spiking, resulting most frequently in acute finger and ankle injuries, respectively.